Development of a Fluid Material Pocket Book to Improve Understanding Flood Disaster Mitigation - Humairah Mustaqim Asma; Jasruddin Jasruddin; Palloan Pariabti (Postgraduate, University of Mataram, 2024)
Research has been carried out on the development of a pocket book on flood mitigation physics. The aims of this research are: to produce a decent pocket book on flood mitigation physics, to produce a practical pocket book, and to increase understanding student disaster. The subject of this research was the development of a pocket book on flood mitigation physics, while the test subjects were 28 students in class XI Science at SMA Negeri 12 Makassar. The development model used in this research is the 4D model. The instruments used were pocket book validation sheets, practitioner assessment questionnaires (educators/teachers), and flood disaster understanding test instruments. The eligibility criteria for pocket books are seen from the aspect of their validity. The practicality criteria are seen from practitioners' assessments, and the effectiveness criteria are seen from increasing students' understanding of disasters. Based on the results of the analysis, conclusions were drawn: the pocket book on flood mitigation physics that was developed was declared valid and suitable for use with minor revisions; pocket book is in the very good category; Students' ability to understand disasters analyzed using N-gain obtained an average value of 0.57, which is in the high category. This means that there is an increase in students' ability to understand flood disasters. In this way, the pocket book on physics for flood disaster mitigation that has been developed can increase students' understanding of disasters